ARTIFICIAL HYDROGEOLOGICAL WINDOWS AS A SOURCE OF BUCHAK-KANIV AQUIFER’S POLLUTION IN THE NORTH-EAST OF UKRAINE - Chomko, D.; Chomko, F.; Cherkashyna, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A new method for determining the location of artificial hydrogeological windows in the roof and base of the aquifer has been proposed. As an example, the Buchak-Kaniv aquifer is given. This aquifer is widespread in the north-eastern part of Ukraine and is the main source of water supply for the region. In our opinion, pollution of the Buchak-Kaniv aquifer can occur primarily through artificial hydrogeological windows in its roof and bottom. In order to determine the location of artificial hydrogeological windows, factor analysis of the chemical composition of groundwater aquifer is used. The analysis was first carried out in places where it is precisely known about anthropogenic contamination of the aquifer with oil products and associated waters through artificial hydrogeological windows (for example, oil or other wells). As a result, a number of influential factors weighing more than 10% were identified. Further, in other areas factor analysis is also carried out using the same set of components of the chemical composition of groundwater. The coincidence of influencing factors indicates the theoretical possibility of an artificial hydrogeological window in a given area. In addition, various options for the distribution of pollutants over the horizon area are considered. The identification of these windows is important for identifying sources of aquifer pollution. Especially attractive will be the use of this method in areas where old (working and closed) oil, gas and oil-gas condensate fields are located.